DESCARTES’ COMPREHENSION OF HUMAN NATURE IN «DISCOURSE ON THE METHOD» - A. M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to analyze the text "Discourse on the Method" as one of the first experiences of understanding human’s nature in modern age philosophy. The condition of realization the designated purpose is to solve the following problems: 1) To Define the diversity of Descartes position on the issue of essentiality to the true knowledge of human nature; 2) To find out the manner influence of methodology of understanding the mathematical truth to the way of interpretation of human nature; 3) To clarify the question of Descartes awareness of boundaries rationalist methodology in understanding of human nature. Methodology. As the methodological base is proposed to use the heuristic potential of phenomenology and existentialism, as well as those publications of foreign Descartes’ researchers of recent times, which introduce the new way for understanding of Descartes’ philosophical heritage. Scientific novelty. For the first time ever in the scientific literature Descartes text "Discourse on Method" becomes the object of special attention as a form of deployment the substantial request for the development of the anthropological project. The affinity and heredity of philosophical doctrines of Aristotle and Descartes on the problem of human nature are accented that is the recognition of the key importance of the need for truth in human nature. It is argued that beyond Descartes’ vision there was no limitation of rationalistic methodology during the comprehension of human nature. Conclusions. The implemented analysis confirms the validity of the thesis about text of the "Discourse on Method" by Descartes as a request of substantial unfolding of the anthropological project. The determining influence methodology of comprehension the mathematical truths to the way of interpretation of human nature were shown. The fact of Descartes’ awareness the limitation of methodology of mathematics in the understanding of human nature and irreducibility the philosopher’s position to the thesis of the res cogitans was emphasized. The attention of manifestations to the last provides a reasonable basis for the specification of his anthropological searches as going beyond the stereotypes of their era.